Effect of Copper Ions upon the Sorption of Amino Acids onto a Fumed Silica Surface - Nataliya M. Vlasova; Ol'ga V. Markitan (Adsorption Science & Technology)
The sorption of some amino acids (Aa) onto a fumed silica surface in the presence of copper ions was studied over the pH range 4–8. The adsorption process was interpreted in terms of the surface complexation theory using the basic Stern model (BSM). Equilibrium parameters were determined using the GRFIT program package. Only basic amino acids such as arginine, lysine and ornithine were sorbed from individual aqueous solutions onto the silica surface. Their sorption was modelled in terms of outer-sphere surface complexes. All these amino acids were sorbed onto silica in the presence of copper ions. Modelling of the amino acid sorption was based on ternary surface complexes. This allowed us to simulate the experimental data at different molar ratios Cu 2+ :Aa (1:1 and 1:2) over the total pH range studied.